Answer:
1489.2
Step-by-step explanation:
9*102-5.6*102=
102(9+5.6) =
102(9.0+5.6) =
102(14.6) =
102*14.6=
14.6*(100+2) =
(14.6*100+14.6*2) =
(1460+(14+.6) *2) =
1460+(28+1.2) =
1460+(28.0+1.2) =
1460+29.2=
1460.0+
29.2
=1489.2
There are no real solutions to that equation.
Answer:
-3+2sqrt7
-3-2sqrt7
Step-by-step explanation:
x^2+6x-9=10
x^2+6x-9-10=0
x^2+6x-19=0
ax^2+bx+c=0
a=1 b=6 c=-19
As cannot be solved by completing square we will use quadratic equation
x= (-b+sqrt(b^2-4ac))/2a and x= (-b-sqrt(b^2-4ac))/2a
x= (-6+sqrt(6^2-4*-19))/2 and x= (-6-sqrt(6^2-4*-19))/2
x=(-6+sqrt(36+76))/2 and x=(-6-sqrt(36+76))/2
x=(-6+4sqrt7)/2 and x=(-6-4sqrt7)/2
x=(-3+2sqrt7) and x=(-3-2sqrt7)
x=2.29 and x= -8.29
Hello there,
I believe the answer would be 17×6 - 6(9+14)(6)/2 = 102 -414 = -312 but i am not 100% Sure!! Sorry if I am wrong!
Hope I helped